SPECIALIZED PRODUCT FOR WATER-SALT BALANCE IMPROVEMENT IN THE BODY OF WORKERS OF HOT WORK SHOPS OF METALLURGICAL ENTERPRISES - Avstrievskikh A.N. (Техника и технология пищевых производств)
A concentrate of non-alcoholic beverage has been developed to improve the water-salt balance in the body of workers of hot work shops of metallurgical enterprises. The recipe composition of the drink which includes active forms of minerals - magnesium, sodium, potassium and chlorine - is scientifically grounded. The composition includes organic acids such as lemon acid and apple acid to ensure faster and full absorption of minerals. Production technology includes the preparation of raw material, its dosing and sieving, mixing of components, quality control, prepackaging, packing, marking and storage. The use of a high capacity mixer under moderate technological conditions ensures homogeneity of the mixtures obtained and the quality of the product. Sanitary hygienic and sanitary-toxicological studies of the beverage concentrate safety were carried out at the end of 15 months of storage and showed the compliance of the tested factors with permissible standards. Established have been shelf life, storage conditions (1 year in a dry place at 25 ± 5°С) and nutritional value characterizing the functional property of a specialized product. According to thedeveloped methodical recommendations one glass (200 cm3) of the reconstituted drink is consumed by workers 5 times during the shift which ensures guaranteed supply of the body with necessary nutrients providing 60% of sodium, 48% of potassium, 50% of magnesium, 56% of chlorides of daily requirements. The effectiveness of a specialized product in the program of therapeutic- preventive nutrition in organized groups of workers at hot work shops of metallurgical enterprises is shown. The drink concentrate is approved and produced at the enterprises of the "Art Life" company in the city of Tomsk.